A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides - Conway, Kevin W.; Kottelat, Maurice (Zootaxa, 2007)
Psilorhynchus robustus, new species, is described from the Ataran River drainage, Myanmar. It is distinguished by the presence of a large dark blotch situated posterodorsal to opercle opening, the upper lip separated from the rostral cap by a shallow groove, and 9 branched dorsal-fin rays. The status of Psilorhynchoides Yazdani, Singh & Rao is discussed.